The Influence of Talent Management and Competency on Employee Performance in the Sabang Type a Class II Navigation District Office with Organizational Cultureas a Mediation - Ricky Hasballah; Mahdani; Sofyan (International Journal of Asian Business and Management, 2024)
This research aims to examine the influence of talent and competency management on employee performance at the Sabang Class II Type A navigation district office with organizational culture as a mediating variable. The population in this study was all ASN of the Class II Sabang Navigation District Office, totaling 155 people. Determining the sample in this study used the number of indicators (24) x 5 method so that the number of samples in this study was 120. The sampling technique used was probability sampling. The research model was analyzed using the SEM application with the help of the Amos program. The research results show that talent and competency management directly have a positive effect on organizational culture. The performance of the Sabang Type A Class II Navigation District Office employees is influenced positively and significantly by talent management, competency and organizational culture. Organizational culture partially mediates the influence of talent and competency management on the performance of Sabang Type A Class II Navigation District Office employees. Effective management of organizational culture can act as a powerful driver for improving employee performance through better application of their talents and competencies. The results of this research show the importance of paying attention to these factors simultaneously in an effort to improve employee performance and strengthen organizational culture. The results of this research can contribute to updating theory and in particular, which also produces solutions for research objects